Etomidate in the management of severe Cushing's disease and MRSA bacteraemia in a district general hospital in the United Kingdom. (12th September 2019) - Wong, Stephanie Wei Ping; Yap, Yew Wen; Narayanan, Ram Prakash; Al-Jubouri, Mohammad; Grossman, Ashley; Daousi, Christina; Mahgoub, Yahya
Abstract : Summary: We report our experience on managing a case of florid Cushing's disease with Methicillin-resistant Staphylococcus aureus (MRSA) sepsis using intravenous etomidate in the intensive care unit of a UK district general hospital. Learning points: Severe Cushing's syndrome is associated with high morbidity and mortality. Etomidate is a safe and effective medical therapy to rapidly lower cortisol levels even in the context of severe sepsis and immunosuppression. Etomidate should ideally be administered in an intensive care unit but is still feasible in a district general hospital. During treatment with etomidate, accumulation of serum 11β-deoxycortisol (11DOC) levels can cross-react with laboratory cortisol measurement leading to falsely elevated serum cortisol levels. For this reason, serum cortisol measurement using a mass spectrometry assay should ideally be used to guide etomidate prescription.